Immune therapy of non-small cell lung cancer. The future. (September 2015) - Bobbio, Antonio; Alifano, Marco
Graphical abstract: Abstract: Surgery is still the best treatment option of lung cancer but only one third of patients are operable and prognosis remains mediocre in operated patients, with the exception of initial stages. Medical treatment is fast moving toward new frontiers. New insights in the biology of cancer development led to discovery of new drugs, which are more effective as compared to conventional platinum based chemotherapy. A new approach to immunotherapy based on immune-check point represents a remarkable innovation in lung cancer treatment. Initial trials with anti PD-1 antibodies in metastatic patients provided results never observed with previously known drug categories. Several key question need to be answered to identify patients most likely to respond to anti PD-1/anti PD-L1 treatments, to assess the role of combined treatment modalities including immune check point receptor block (associations with surgery, chemotherapy, ITKs), and to boost host immune response, possibly by lowering his systemic inflammation and improving nutritional status.